Changes in tobacco industry advertising around high schools in Greece following an outdoor advertising ban: a follow-up study. Issue 5 (6th November 2012) - Vardavas, Constantine I; Girvalaki, Charis; Lazuras, Lambros; Triantafylli, Danai; Lionis, Christos; Connolly, Gregory N; Behrakis, Panagiotis
Abstract : Background: As tobacco advertising bans are enacted in accordance with the Framework Convention on Tobacco Control, it is essential to assess enforcement and how the industry may circumvent such measures. Objective design: During this longitudinal study, we compared the characteristics of points-of-sale (POS) advertising within 300 m of all high schools in Heraklion, Greece before (n=101 POS and 44 billboards in 2007) and after (n=106 POS in 2011) an outdoor advertising ban was implemented in 2009. Cigarette advertisements in all retailers near all high schools were assessed. Results: Following the ban, tobacco industry billboards around schools were eradicated (from 44 to 0). The proportion of POS that had external advertisements dropped from 98% to 66% (p<0.001), more so in regulated convenience stores (from 97% to 35%, p<0.001) than in kiosks (98% to 92%, p=0.192), which were exempt from the ban. The proportion of convenience stores that had advertisements on the door (79.5% to 20.4%, p<0.001), ads that could be seen from the street (92.3% to 22.4%, p<0.001) or illuminated exterior ads (46.2% to 10.2%, p<0.001) was also significantly reduced. Overall, the average number of exterior advertisements per POS fell from 7.4 to 3.9 (p<0.05). This reduction was noted in regulated convenience stores (4.8±3.0 vs 0.9±2.1, p<0.001) and in unregulated kiosks (9.0±6.7 vs 6.5±4.5, p=0.019). Conclusions: The outdoor advertising restriction in Greece has led to a reduced number of tobacco advertisements per POS, and the eradication of billboard advertising. Nevertheless, there is a need to regulate kiosks, which were identified as a key vector for tobacco advertising, and to increase compliance among regulated convenience stores.